Control system of the CYRCé beamlines. (1st May 2022) - Maazouzi, C.; Adam, T.; Bouquerel, E.; Pellicioli, M.; Schuler, J.; Rousseau, M.; Traykov, E.; Graehling, P.
Abstract: The first two extension beamlines from the CYRCé cyclotron have been developed and recently commissioned at IPHC Strasbourg. One beamline is devoted to radiobiological experiments, the PRECy project, while the other one is for testing silicon detector modules in the framework of the CMS experiment. The development of the control system of these beamlines is reported in this paper.